Insect-Based Foods: A Comprehensive Review on Nutritional Benefits and Environmental Sustainability - S Isaac, Anvy; Wilson, Ivan; Vaibhav Singh, Vibhanshu (International Journal of Entomology, 2025)
The growing population demands and environmental concerns associated with traditional protein sources have prompted the exploration of alternative and sustainable food sources. The purpose of this comprehensive review is to highlight the nutritional benefits and sustainability of insect-based foods as a promising solution. Global population growth necessitates innovative approaches to meet the demand for nutritious and sustainable protein sources. There are numerous challenges associated with traditional livestock farming, including land use inefficiency, high water usage, and greenhouse gas emissions. As a result, edible insects have emerged as a viable alternative, providing proteins (35-77% of dry matter), healthy fats (10-50%), essential amino acids, and micronutrients such as iron (up to 31mg/100g) and zinc (up to 20mg/100g), vitamins, and minerals. In contrast to livestock, which requires 22,000-43,000 liters of water to produce 1 kg of beef, insect farming consumes significantly less water and land resources. Insects have the potential to address nutritional deficiencies and strengthen food security as they are recognized for sustainable production. The study thoroughly investigates the literature addressing environmental and sustainability concerns associated with edible insect farming, using a rigorous bibliometric and scientometric analysis via Vos viewer. With the help of Vos Viewer, it was possible to identify the geographical distribution of countries that contributed to the field of edible insects and their acceptance, as well as the top ten documents in this field with the most citations and mostly used keywords in this field of research. Future research and implementation strategies will be able to benefit global food security and environmental conservation through these alternative protein sources.
Keywords: VOS viewer; Edible insects; Consumer acceptance; Environmental sustainability; Sustainable food sources; Nutritional composition of edible insects